Early child care, maternal labor supply, and gender equality: A randomized controlled trial - Henning Hermes; Marina Krauß; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (Halle Institute for Economic Research (IWH), 2024)
We provide experimental evidence that enabling access to universal early child care increases maternal labor supply and promotes gender equality among families with lower socioeconomic status (SES). Our intervention offers information and customized help with child care applications, leading to a boost in child care enrollment among lower-SES families. 18 months after the intervention, we find substantial increases in maternal full-time employment (+160%), maternal earnings (+22%), and household income (+10%). Intriguingly, the positive employment effects are not only driven by extended hours at child care centers, but also by an increase in care hours by fathers. Gender equality also benefits more broadly from better access to child care: The treatment improves a gender equality index that combines information on intra-household division of working hours, care hours, and earnings by 40% of a standard deviation, with significant increases in each dimension. For higher-SES families, we consistently observe negligible, insignificant treatment effects.
Keywords: C93; J13; J18; J22; 330; child care; gender equality; maternal employment; randomized controlled trial